APOPTOSIS ROLE IN FORMING RADIOIODINE RESISTANCE IN DIFFERENTIATED THYROID CANCER - K.A. GARIPOV; Z.A. AFANASIEVA; A.D. GAFIULLINA (Avicenna Tajik State Medical University, 2020)
According to studies, 25-66% of patients with metastatic highly differentiated thyroid cancer (DTC) develop partial or complete resistance of metastases to therapy with radioactive iodine. The review discusses the molecular mechanisms for the involvement of various apoptosis proteins in the formation of radioiodine resistance in patients with DTC, as well as the molecular mechanisms of the action of multikinase inhibitors, with a range of therapeutic effects from complete tumour regression to stabilization, on apoptosis. Considering the literature on the ambiguous role of apoptosis in the formation of radioiodine resistance in DTC, required further examination of its molecular mechanisms, its relationship with such a process as autophagy, the effect of multikinase inhibitors on its molecular basis and on overcoming iodine resistance. Studying the mechanism of apoptosis regulations gives a chance to find new targeted aims exposure in its individual stages in order to regulate or correct them.